A Meta-Analysis of the Problem-Based Learning Model to Enhance Students' Creative Thinking Skills - Elsa Sabrina; Maksum, Hasan; Waskito (The Indonesian Journal of Computer Science, 2024)
This study aims to investigate the influence of the Problem Based Learning (PBL) model on enhancing students' creative thinking skills. Meta-analysis method was employed to collect and analyze data from 17 relevant articles published in online journals between 2018 and 2023. The analysis results indicate that the implementation of the PBL model has a significant impact on enhancing students' creative thinking skills, with an effect size value of 0.40 categorized as a moderate effect. The implications of these findings underscore the importance of integrating the PBL model into educational approaches to facilitate the development of students' creative thinking skills in various educational contexts.